Raman imaging studies on the adsorption of methylene blue species onto silver modified linen fibers. (12th April 2017) - Fateixa, Sara; Wilhelm, Manon; Jorge, Alípio M.; Nogueira, Helena I. S.; Trindade, Tito
Abstract : We demonstrate in this research that surface‐enhanced resonance Raman scattering combined with Raman imaging can be effectively used for analysis of distinct forms of organic dyes in antimicrobial Ag‐loaded textile fibers. The potential of this approach, as a non‐destructive characterization method of fabrics, was evaluated with Raman studies performed on the molecular forms of methylene blue (MB), used here as the organic dye model. On the basis of the surface‐enhanced Raman scattering spectra of MB monomers and dimers, the Raman imaging of Ag‐loaded linen fibers previously treated with MB solution was performed and then used for identification of the adsorbate species in distinct regions of the substrates. A semi‐quantitative analysis is then performed by considering the area of the Raman bands ascribed to the MB molecular forms and image analysis applied to Raman images. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Surface‐enhanced resonance Raman scattering (SERRS) coupled with Raman imaging can be successfully used to identify distinct forms of organic dyes adsorbed within antimicrobial linen fibers enriched in Ag nanoparticles. The potential of this approach as a non‐destructive characterization method of fabrics was evaluated with Raman studies performed on the molecular forms of methylene blue (MB), used here as the textile colorant. Our results demonstrate that by using SERRS imaging it is possible to identify the adsorbate species in distinct regions of the substrates.